AB0913 Agreement study and expert consensus for the clinical picture of chikv infection. (15th June 2017) - Rueda, JC; Angarita, J-I; Pinzon, C; Santos, AM; Saldarriaga, E-L; Rueda, JM; Saaibi, DL; Forero, E; Pelaez-Ballestas, I; Pavía, PX; Londono, J
Abstract : Background: World Health Organization suggested case definitions to suspect and diagnose chikungunya virus infection which are: possible case, probable case and confirmed case. Although useful, when applied in practice, its lack definition for specific joint involvement and absence of other systemic symptoms apart from fever, leads to a broad clinical spectrum which increases the need for laboratory tests. Objectives: To establish agreement on clinical criteria of CHIKV infection based on clinical expertise of specialists from affected areas of Colombia and to develop a set of clinical criteria. Methods: A group of specialists in rheumatology, epidemiology and bacteriology from different parts of Colombia with experience in diagnosis and treatment of CHIKV patients from the epidemic of 2014–2015 met to reach agreements on clinical characteristics of CHIKV infection. A series of questions were formulated and agreement in percentage was calculated on the following answers: totally agree, agree, not in agree or disagree, disagree and totally disagree. Agreement was set when the sum to the answers totally agree and agree or disagree and totally disagree of was ≥50%. When agreement was not reached, the moderator performed a discussion with the opinions of the confronting members of the group and after that reformulated the question. This procedure was made until agreement was reached. With the results a set of clinical criteria was proposed. Results: The agreement percentage to the formulated questions are depicted in table 1 . Disagreement was achieved with mucosal imvolvement (100%), G/I involvement (88%), and arthralgia and arthritis in shoulders (63% and 100%) and in elbows (100%). Conclusions: Agreement was achieved in abrupt onset of symptoms, and the presence of fever, rash, myalgia, fatigue, and symmetrical arthritis or arthralgia of wrists, hands, knees, ankles and feet. A set of clinical criteria was proposed (figure 1). Disclosure of Interest: None declared